Evaluation of plant protection chemicals and botanicals for management of Alternaria blight in yellow sarson (Brassica campestris) - S.K. SINGH and H.K. SINGH, DHARMENDRA KUMAR*, YASHWANT K. BHARATI (Indian Phytopathology, 2016)
Necotrophic habit of plant pathogenic Alternaria spp. is known to cause extensive damage and yield loss of rapeseed-mustard. During study of dominance of Alternaria spp. in infected tissues of rapeseed- mustard in Uttar Pradesh, Alternaria brassicae, A. brassicicola and A. raphani were found associated with variable frequency. Conidial population of A. brassicae was found high in infected tissues. Evaluation of 15 genotypes of rapeseed-mustard showed the moderately susceptible response of 12 genotypes and susceptible response of 3 genotypes against the leaf blight. Three foliar spray of Propiconazole, Iprodione, Carbendazim + mancozeb, Hexaconazole, Mancozeb, Garlic bulb extract, Neem oil, Karanj seed extract and leaf extract of Eucalyptus, Dhatura and Madar effectively reduced the disease severity on leaves and pods in yellow sarson. However maximum disease control was obtained by the three spray of 0.1% Propiconazole. Extracts of garlic bulb, Eucalyptus leaf and neem oil was also found effective against the Alternaria blight and could be a substitute of fungicides.